TINDAK TUTUR DIREKTIF DALAM ANIME HYPNOSIS MIC -DIVISION RAP BATTLE- RHYME ANIMA: PERBEDAAN CARA ICHIRO YAMADA DAN SAMATOKI AOHITSUGI DALAM MEMIMPIN ANGGOTA TIM - Widyati, Adita Ramaniya; Septiana, Amelya (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2025)
The anime Hypnosis Mic -Division Rap Battle- Rhyme Anima presents leadership dynamics through the use of directive speech acts by two division leaders: Ichiro Yamada from Buster Bros!! and Samatoki Aohitsugi from Mad Trigger Crew. This study aims to explore how directive speech acts are used by the leaders to guide their team members while reflecting their respective leadership styles. A descriptive qualitative approach was applied to analyze dialogues taken from several episodes of the anime. The results show that Ichiro employs a friendly and supportive communication style, while Samatoki demonstrates an authoritative manner with firm and direct word choices. These findings illustrate the relationship between the use of directive speech acts and the portrayal of leadership roles in the story. Furthermore, this study highlights how variations in speech style reflect each leader’s personality and underlying values. It also provides new insights into how language functions as a means of constructing group dynamics and maintaining social hierarchy within a narrative context. The findings are expected to serve as a reference for future studies in pragmatics and discourse analysis, particularly in literary works and Japanese popular media.